Association Between Sexual Problems and Relationship Satisfaction Among People with Cardiovascular Disease. Issue 5 (1st May 2017) - Byrne, Molly; Murphy, Patrick; D'Eath, Maureen; Doherty, Sally; Jaarsma, Tiny
Abstract: Background: Relationship satisfaction is generally positively correlated with sexual satisfaction, but this relation has been poorly examined in people with cardiovascular disease who are at increased risk of sexual problems compared with the general population. Aim: To document reported changes to sex after a diagnosis of cardiac disease and determine whether there is an association between sexual function and relationship satisfaction. Methods: Semistructured telephone interviews focused on relationship satisfaction and sexual problems were conducted with 201 people with cardiovascular disease who were currently in a sexual relationship with one main partner and were recruited from six hospital cardiac rehabilitation centers in Ireland. Comparisons between groups were conducted using t-tests and multivariate analysis of variance for continuous variables and χ 2 tests for categorical variables. Predictors of relationship satisfaction were assessed using multiple linear regression analysis. Outcomes: Data were gathered on demographic and clinical variables, sexual problems, and relationship satisfaction, including satisfaction with the physical, emotional, affection, and communication aspects of relationships. Results: Just less than one third of participants (n = 61, 30.3%) reported that sex had changed for the worse since their cardiac event or diagnosis, with approximately half of these stating that this was a serious problem for them. Satisfaction with relationships was high among patients surveyed; more than 70% of the sample reported being very or extremely satisfied with the physical and emotional aspects and showing affection during sex. Satisfaction with communication about sex was lower, with only 58% reporting being very or extremely satisfied. We did not find significant associations between reporting of sexual problems or deterioration of sex as a result of disease and relationship satisfaction. Clinical Implications: Cardiac rehabilitation programs should address these sexual problems, potentially by enhancing communication within couples about sex. Strengths and Limitations: The strength is that data are presented on the sexual experiences and relationship satisfaction of a relatively large sample of people diagnosed with cardiac disease, a relatively underexplored research area. Limitations include the possibility of selection bias of study participants and bias associated with self-report measurement. Conclusions: Sexual problems were significant in this population but were not related to relationship satisfaction in this cross-sectional survey.